2015
DOI: 10.3390/ijns1020069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hematocrit and Total-Spot Volume on Performance Characteristics of Dried Blood Spots for Newborn Screening

Abstract: Dried blood spots (DBS) have been used in newborn screening (NBS) tests for over 50 years. The Newborn Screening Quality Assurance Program (NSQAP) at the Centers for Disease Control and Prevention (CDC) conducted studies to assess the individual impacts of hematocrit and total-spot volume on characteristics of DBS samples. Per-punch serum volumes decreased 27%, RBC volumes more than doubled, absorption times increased over 300%, and spot diameters decreased marginally between the hematocrits of 40% to 65%. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 12 publications
(9 reference statements)
1
71
1
1
Order By: Relevance
“…Despite this, however, there was still considerable inter-individual variation in the estimated volume of blood in 3 mm DBS punches from 30 different individuals using this assay (CV % 32%) (Figure 2). [8,11,23] The estimated volume of blood in a 3 mm disc obtained from a conventional newborn screening blood collection paper (903 paper) in a previous study was %3 μL, [5] which is notably higher than the estimates calculated for the 903 paper from the gravimetric analysis in the current study (2.2 AE 0.1 μL). [22] Our findings are in line with previous studies using other DBS systems that have also reported variations in Table 1.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Despite this, however, there was still considerable inter-individual variation in the estimated volume of blood in 3 mm DBS punches from 30 different individuals using this assay (CV % 32%) (Figure 2). [8,11,23] The estimated volume of blood in a 3 mm disc obtained from a conventional newborn screening blood collection paper (903 paper) in a previous study was %3 μL, [5] which is notably higher than the estimates calculated for the 903 paper from the gravimetric analysis in the current study (2.2 AE 0.1 μL). [22] Our findings are in line with previous studies using other DBS systems that have also reported variations in Table 1.…”
Section: Resultscontrasting
confidence: 71%
“…[10][11][12]21] One such method is an on-card approach to assess the hematocrit of DBS in order to correct for sample volume, which has previously been shown to improve the precision and the accuracy of the results. As a result, several methods have been developed to account for such DBS volume variations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Gelb's letter also states that “there is no correlation seen in one enzymatic activity compared to another… variation in white cell count or other DBS quality factors are not dominant effects” without providing appropriate supporting data. This statement is totally incompatible with multiple peer reviewed publications to the contrary [7], [8], [9], [10]. Newborn screening for LSDs by either MS/MS or DMF results in a relatively high rate of presumptive positive results, because cut-offs are near the low limits of quantification and must be set conservatively to take into account well-documented pre-analytical variables and avoid false negatives [2].…”
mentioning
confidence: 98%
“…Absorption time was measured with a stopwatch, which was started when the blood touched the filter paper and stopped when any shine from the liquid blood was no longer visible on the surface. Absorption diameters were measured at the widest diameter [6].…”
Section: Preparation Of Dbss On Filter Paper Treated With Gluementioning
confidence: 99%